Efektivitas konseling behavioral dengan teknik modelling dalam menangani perilaku maladaptif siswa madrasah aliyah negeri - Nadila, Olga Rizki; Lubis, Saiful Akhyar (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2024)
This research aims to determine the effectiveness of modeling techniques in overcoming maladaptive behavior in class X students at Madarasah Aliyah Negeri. The method used in this research was pre-test post-test only control group design with sampling using a purposive sampling technique, taking a sample of 20 students with the lowest scores and high levels of maladaptive behavior based on the results of the pretest analysis, with the reason that purposive sampling increases methodological accuracy and trustworthiness of data and results by matching the sample to the aims and objectives of the study. The sample used was 20 class X students. Data collection was carried out using a maladaptive behavior questionnaire which has been proven valid and reliable. From the results of research using the t test, it is known that behavioral counseling using modeling techniques is effective in overcoming maladaptive behavior. This can be seen from the results of research data analysis, which shows that tcount = 3.806, and ttable with db = 18 and a significance level of 0.05 or 5% is 2.101, so it is obtained that tcount > ttable (3.806 > 2.101) from the post test results of the experimental group is greater than control group. So the conclusion of the alternative hypothesis is accepted in other words. Behavioral Counseling with Modeling Techniques is Effective in Overcoming Maladaptive Behavior in Class X State Madrasah Aliyah Students.